The Application of Training Module about School Children’s Central Vision Examination for Increasing Elementray School Teacher’s Knowledge and Skill Level to Detect Poor Visual Acuity - Wijayaningrum Wijayaningrum; Trilaksana Nugraha; Sri Inakawati; Hari Peni (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Uncorrected refractive error children can lead amblyopia. To improve detection of refractive error in children, active participation of primary school teachers needed. These teachers need a guidance applied in a training to detect children poor visual aquity by examining central vision. This study objective is to prove the increase of both knowledge and skill level of school teachers in examining central vision to detect children poor visual aquity after the application of training modules. Methods: This is a quasy experimental study combined with indepth interview to take qualitatif data. One group pretest and posttest design of 45 subjects (primary school teachers from Semarang) who received a book dan tutorial compact disc modules applied in a training in April, 2013. Level of knowledge measured using questionnaire and level of skill measured using checklist. Results: Results showed both knowledge and skill level before application of training modules compared to after had significant difference (Wilcoxon, p<0,005). Qualitatif data informed a few of teachers didnot applied the skill and knowledge after the training. Conclusion: There were significant increase of primary school teachers’ knowledge and skill level in examining central vision to detect children poor visual aquity after the application of training modules. Refreshing training should be scheduled periodically to maintain their knowledge and skill. Keywords: Children visual aquity, teachers detect vision, central vision training modules